عوامل انتشار المذهب المالكي في المغرب الإسلامي بين القرنين (2و5ه/8و11م) Factors For The Spread Of The Maliki School Of Thought In The Islamic Maghreb Between The Two Centuries (2 And 5 Ah/8 And 11 Ad) - مصطفى, زروق (جامعة الوادي university of eloued, 2023)
يعتبر موضوع: "عوامل انتشار المذهب المالكي في المغرب الإسلامي بين القرنين 2و5ه/8و11م" ضمن المواضيع التاريخية والدينية البالغة الأهمية، لأن دراسته تمكننا من الإطلاع على حقبة زمنية انتشر فيها هذا المذهب، في بيئة سياسية وفكرية مضطربة، جعلت التمسّك به الملاذ الآمن، لتحقيق الاستقرار السياسي والتطور الفكري، باعتباره المرآة العاكسة للمنطقة التي عاش فيها الرسول صلى الله عليه وسلم، وأصحابه من بعده، وهذا ما دفع المغاربة إلى اعتناقه والولوع به. ورغم كثرة التحديات التي عرفتها المنطقة في هذه الفترة، إلا أن فقهاء المالكية بقوا على العهد، متبعين سيرة إمامهم مالك، القائمة على الأمر بالمعروف والنهي عن المنكر، وقول الحق للسلطان الجائر، ولو كلفهم ذلك فقدان مناصبهم أو حياتهم، وهذا ما زاد من قيمتهم، ورفع من شأنهم لدى العامّة الذين اقتدوا بهم، وطلبوا فتاواهم حول النوازل التي ألمّت بهم. The issue of : (Factors for the spread of the Maliki school of thought in the Islamic Maghreb between the two centuries 2 and 5 AH/8 and 11 AD) is considered among the important historical and religious topics, because its study enables us to see an era in which this doctrine spread in a turbulent political and intellectual environment, which made adhering to it the best ways to achieve political stability and intellectual development and this what prompted the Moroccans to embrace it. Despite the many challenges that the region witnessed during this period, the Maliki jurists remained on the covenant, following the biography of their Imam Malik, which is based on enjoining good and forbidding evil and telling the truth to the unjust sultan, even if it cost them to lose their positions or their lives and this increased their value and raised their status. To the common people, who followed them and asked for their
مقال
Keywords: المغرب الإسلامي ; المذهب المالكي ; فقهاء المالكية ; الفقه المالكي; The Islamic Maghreb ; the Maliki school of thought ; the Maliki jurists ; the Maliki jurisprudence